Kalimat Transitif-Intransitif: Analisis Kontrastif antara Bahasa Arab dan Bahasa Indonesia - Mukminin, Amir; Bashori, Ahmad (Aphorisme: Journal of Arabic Language, Literature, and Education, 2022)
This study aims to examine more deeply the division of transitive-intransitive sentences in Arabic and Indonesian, as well as the similarities and differences between the two. The research method used is a qualitative method with the type of library research. This study's results indicate similarities and differences in transitive-intransitive sentences between Arabic and Indonesian. In terms of the similarities, the writer considers it in terms of the position of transitive-intransitive sentences, which are types of sentences that are seen from the need for the object of the sentence, and in terms of the division of the sentence, as well as in terms of how to change intransitive sentences into transitive sentences. In terms of the writer's difference in terms of the different sentence structure patterns between Arabic and Indonesian, there are unique signs of transitive-intransitive sentences in Arabic that do not exist. It exists in Indonesian, and there is a specification in the meaning of an intransitive sentence in Arabic which does not exist in Indonesian.